Rock magnetism in two loess–paleosol sequences in Córdoba, Argentina - Rouzaut, Sabrina (2014)
This work presents new rock magnetic results along two loess–paleosol profiles in nearby locations in Argentina. The main objective of this study is to compare the magnetic signals and mineral content of two profiles and determine if the climate during Marine Isotope Stage 5 (MIS 5) and MIS 3 were similar to the present one. The two profiles are located in two different geomorphological settings, with effects on the water saturation characteristics and seasonality. Selected samples taken at these profiles were analyzed using laboratory procedures and environmental magnetism parameters to determine the climatic influence during the Late Pleistocene. Despite their proximity there are several differences between both profiles, such as their depth and geomorphological positions among others. The results of these analyses led to the following conclusions: climate conditions during MIS 5 were very similar to those of the present conditions. The hypothesis for this area suggests a slight increase in the magnetic signal associated with the generation of small amounts of magnetite and preservation of detrital magnetite and titano-magnetite. The results in this paper show a slight gain in the buried soils of Córdoba that would confirm the hypothesis.